Investment in Signings in LaLiga: Analysis of SportsDirectors’ Efficiency - Megía-Cayuela, Daniel (Wiley, 2025)
Objectives: This article evaluates the efficiency in professional football related to the financial and sports management of clubs.The study framework is the Spanish First Division in the 2022/2023 season. Methods: The methodology applied is a decision envelopment analysis (DEA) that allows analyzing the efficiency in the decision-making bodies (DMUs) by linking the position at the final table with different variables on the management of the footballers.Unlike previous works, we include a cluster analysis with an efficiency ranking that allows us to know what the commoncharacteristics of these clubs and their sporting and financial strategies are. Results: The main conclusion with this proposal is the low rate of average in efficiency, but we consider there are two keys to gethigh levels of success: the numbers of operations of transferring and applying a polity of zero cost signing new football players. JEL Classification: D52, D57, F61, G14, C88, L83
Funding for open access charge: Universidad de Málaga / CBUA
Keywords: Fútbol; Gestión; Deportes; Economía; Cluster; Data envelopment analysis; Efficiency scores; Player signings; Sport director